2010
DOI: 10.1080/08997761003590457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Celebrity Media Exposure on Box-Office Performance

Abstract: This article examines the relation between box-office performance and celebrity media exposure, as measured by appearances in the celebrity magazine, People. This study employs variables that capture different time periods to test whether People magazine appearances were merely part of a general promotional effort by a studio or whether appearances reflected the popular appeal of the actor. The results indicate that promotional appearances do not significantly affect box-office revenues. In fact, it is the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Zufryden (1996) analyzed the effects of advertising and the intensities of the theatre distribution on the success of a film. Treme (2010) analyzed the effects of media exposure of a celebrity in the magazine, "People" (2020). They found that in most cases the media exposure of the celebrity involved in the movie plays a vital role in determining the fate of the film rather than promotional advertisements before the release of the film.…”
Section: Previous Workmentioning
confidence: 99%
“…Zufryden (1996) analyzed the effects of advertising and the intensities of the theatre distribution on the success of a film. Treme (2010) analyzed the effects of media exposure of a celebrity in the magazine, "People" (2020). They found that in most cases the media exposure of the celebrity involved in the movie plays a vital role in determining the fate of the film rather than promotional advertisements before the release of the film.…”
Section: Previous Workmentioning
confidence: 99%
“…Faulkner and Anderson 1987;Litman and Kohl 1989;Wallace, Seigerman, and Holbrook 1993;Prag and Casavant 1994;Sochay 1994;Sawhney and Eliashberg 1996;Neelamegham and Chintagunta 1999;Basuroy, Chatterjee, and Ravid 2003;Elberse and Eliashberg 2003;Ainslie, Drèze, and Zufryden 2005;Elberse 2007;Hadida 2010;Treme 2010;Karniouchina 2011;Nelson and Glotfelty 2012).…”
Section: Current State Of Researchmentioning
confidence: 99%
“…In the case of MPAs, consumer knowledge is generated through media coverage. Treme (2010) stresses the importance of media coverage of MPAs that is useful to both actors and movie studios.…”
Section: Actor's Media Presencementioning
confidence: 99%
“…As Couldry (1999, p. 59) observed, cultural studies have given only marginal attention to the practices of people rich in economic and cultural capital, compared with the abundance of material on the cultural and media-related practices of the working class. Thus, instead of studying celebrities as agents and respondents, most research efforts have examined fans' consumption of celebrity (e.g., Gray et al 2007) or the effects of celebrity (e.g., Elliott 2011, Treme 2010). …”
Section: Interviewing Celebritiesmentioning
confidence: 99%